Using geostatistical methods for evaluating organic matter reserves in fallow soils - K.G. Giniyatullin; S.S. Ryazanov; E.V. Smirnova; L.I. Latypova; L.Yu. Ryzhikh (Учёные записки Казанского университета: Серия Естественные науки)
In the samples taken layer by layer (every 5 cm) from the old arable horizon of fallow light gray forest soils, the content of organic matter and the bulk density were determined in order to calculate humus reserves. All samples were taken from 50 sampling points distributed along the study site according to a stratified random pattern. The amount of humus reserves was calculated using the geostatistical interpolation methods with regard to the spatial, horizontal, and vertical variability of organic matter content in the old arable horizon, as well as its bulk density and thickness. The results obtained show that the accumulation of soil organic matter (SOM) under deposits occurs primarily in the upper part of the topsoil horizon; the amount of humus that accumulated over 15 years under fallow vegetation is 21% of the total reserve. This paper also discusses the methodological aspects of soil sampling for unbiased estimate of humus reserves.